OVISIDAL ACTIVITY OF EXTRACT ETHANOL NEEM LEAF FOR ASCARIS SUUM - Budiasa, Ketut; Dwinata, I Made; Merdana, I Made; Putra, Kadek Febriana Marta (Buletin Veteriner Udayana, 2021)
The purpose of this research was to determine the ovicidal effect of neem leaves extract (Azadirachta Indica, A. Juss ) on the embryo strength of Ascaris suum eggs. This study using a complete random design with treatment groups, namely P0, P1, P2, P3, P4,  with four replication. Group P0 was treated with physiological NaCl as a negative (-) and group (P1) was treated with physiologic NaCl + albendazole as the positive control (+), (P2) treated with 10% neem leaf extract. The P3 group was treated with 20% neem leaf extract and the group (P4) was treated with 30% neem leaf extract, which was done by soaking the worm eggs. The observation of embryonic eggs of the worm was done on the 15th, 21st and 30th day. The result showed that the neem leaves extract had a significant effect (P <0,05) on the embrionation of A. suum eggs. Further test using Games-Howel test showed the extract of neem leaves at dose 30% most effective reduced the embrionation of A. suum eggs. It can be concluded that neem leaf extract has ovicidal activity against A.suum eggs with in vitro test.